2007
DOI: 10.1080/12538078.2007.10516043
|View full text |Cite
|
Sign up to set email alerts
|

Combined dyeing and antioxidative properties of some plant by-products

Abstract: Abstract.-Aqueous extracts of plant by-products (carrot, onion, black carrot, sage, spinach and thyme) were investigated for dyeing capacity on fibres and for both colorant and antioxidant potential using colorimetric and chromatographic tools, and FTC assay, respectively. Regarding fibres, classical correlations between measured colours and phytochemical patterns of dyeing extracts were verified. Light fastness of onion, sage and thyme samples, evaluated following a normalised test, was very promising conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…With respect to onions, although there has been substantial evidence for the usefulness of extracts, deriving mainly from the outer inedible layers, as antioxidants (Kefalas and Makris 2006;Škerget et al 2009), antibrowning (Lee 2007;Roldán et al 2008) and colouring agents (Guinot et al 2007), no study up to date provided any information on the stability of the major components accounting for the aforementioned properties.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to onions, although there has been substantial evidence for the usefulness of extracts, deriving mainly from the outer inedible layers, as antioxidants (Kefalas and Makris 2006;Škerget et al 2009), antibrowning (Lee 2007;Roldán et al 2008) and colouring agents (Guinot et al 2007), no study up to date provided any information on the stability of the major components accounting for the aforementioned properties.…”
Section: Resultsmentioning
confidence: 99%
“…After long exposure to UV rays as well as several washing steps, this protection might be reduced or even lost. Otaviano et al [43] reported a good UPF (25) for cotton dyed with pomegranate peel extract, but after 10 washing cycles, no UV protection was detected. To address this issue, mordants can be used.…”
Section: Uv Protectionmentioning
confidence: 99%
“…The biological properties of the different types of phenolic compounds make them an extremely interesting group of compounds with potential for use in the textile industry. Beyond their natural coloration ability, these compounds have also been investigated for their potential to impart novel functionalities to textiles, including antimicrobial, antioxidant, ultraviolet (UV) protection, and flame retardance properties, among others [24][25][26][27]. As such, a literature research methodology was completed using the databases Science Direct and Web of Science, and research articles reporting natural dyes containing phenolic compounds applied to textile fabrics were compiled and investigated further.…”
Section: Introductionmentioning
confidence: 99%
“…yapmış oldukları çalışmada organik olarak üretilmiş pamuklu örme kumaşı farklı doğal boyarmadde kaynakları ile boyayarak organik pamuğun çevre dostu özelliğinin korunduğunu ifade etmişlerdir [13]. Kekik bitkisinin birçok farklı türü boyamacılıkta kullanılmakla birlikte özellikle bitkinin dal ve yapraklarında bulunan kimyasal maddeler boyama ve sağlık açısından önemli olduğu ifade edilmiştir [14]. Önem ve ark.…”
Section: Doğal Boyamacılığın Tarihi Insanlık Tarihi Kadar Eskidirunclassified